2014
DOI: 10.1016/j.joa.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of the pulmonary venous and left atrial anatomy with non‐contrast‐enhanced MRI for catheter ablation of atrial fibrillation: Usefulness of two‐dimensional balanced steady‐state free precession

Abstract: The 2D b-SSFP sequence was more useful than the 3D b-SSFP sequence in adequately depicting the PV-LA anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…However, signal void artifact of the PVs frequently occurs using the 3D b‐SSFP sequence due to the off‐resonance caused by the proximity to the lungs. Recently, PV‐LA anatomical imaging without any signal void artifact that could be acquired by non–CE‐MR imaging with a two‐dimensional (2D) b‐SSFP sequence in all healthy volunteers has been reported. This study investigated the feasibility of substituting non–CE‐MR imaging with a 2D b‐SSFP sequence for the CE‐CT for planning the AF ablation procedure.…”
mentioning
confidence: 99%
“…However, signal void artifact of the PVs frequently occurs using the 3D b‐SSFP sequence due to the off‐resonance caused by the proximity to the lungs. Recently, PV‐LA anatomical imaging without any signal void artifact that could be acquired by non–CE‐MR imaging with a two‐dimensional (2D) b‐SSFP sequence in all healthy volunteers has been reported. This study investigated the feasibility of substituting non–CE‐MR imaging with a 2D b‐SSFP sequence for the CE‐CT for planning the AF ablation procedure.…”
mentioning
confidence: 99%
“…Interestingly, TOE was not found to affect procedural outcomes. The usefulness of cardiac CT and MRI in identifying LA thrombus in patients undergoing ablation has been found in other studies 80 81 on top of their benefit in assessing cardiac anatomy and pulmonary vein size and location [82][83][84] and chances of successful outcome (figure 7). 85 …”
Section: Peri-procedural Imaging In Catheter Ablationmentioning
confidence: 81%
“…The incidence of AF has increased from 5.9/1000 person-years in 2001 to 6.9/1000 person-years in 2013. The overall incidence in terms of 1000 person-years increases with increasing age (25.1 for patients between [80][81][82][83][84][85][86][87][88][89] and is also higher for Caucasians (8.1) versus Asians (5.4) and African Americans (4.6).…”
Section: Epidemiology and Risk Factors Increasing Incidence Of Af In mentioning
confidence: 99%
“…Hu et al reported significantly more off-resonance artifacts at the right inferior PV than other PVs and they proposed that differences in lung morphology and distance between the PV and air-containing lung tissue were potential etiologies for the artifacts [ 20 ]. Shigenaga et al reported that artifacts were worse with 3D vs. 2D bSSFP and they considered this related to greater inflow refreshment with 2D [ 21 ].…”
Section: Discussionmentioning
confidence: 99%